Nanoemulsion-based delivery approaches for nutraceuticals: fabrication, application, characterization, biological fate, potential toxicity and future trends. Issue 5 (17th February 2021) - Li, Guotao; Zhang, Zhengyu; Liu, Haofan; Hu, Liandong
Abstract : Edible nanoemulsions to encapsulate, protect and deliver lipophilic functional ingredients are receiving increasing attention in the modern food industry. Abstract : In the modern food industry, people are paying more and more attention to the use of edible nanoemulsions to encapsulate, protect and deliver lipophilic functional ingredients, such as volatile additives, polyphenols, aromas, pigments, proteins, vitamins, oil-soluble flavors, preservatives, etc., which are the current global needs. Nanoemulsions are constructed with droplets of nano range size and they offer many potential advantages over conventional emulsions including the delivery of both hydrophilic and hydrophobic compounds, higher stability, better antibacterial properties, good taste experience, higher affinity, longer shelf-life and improvement of the bioavailability of components. Moreover, they are highly capable of improving the wettability and/or solubility of poorly water-soluble compounds, which may result in better pharmacokinetic and pharmacodynamic properties of nutraceutical compounds. On the other hand, oral nanoemulsions also have certain risks, such as their ability to change the biological fate of biologically active ingredients in the gastrointestinal tract and the potential toxicity of certain ingredients used in their production. This review article summarizes the manufacturing, application, characterization, biological fate, potential toxicity, and future challenges and trends of nanoemulsions, and focuses on nanoemulsion-based nutraceutical delivery approaches suitable for the food industry.